Analisis Kesalahan Menurut Tahapan Kastolan Dan Pemberian Scaffolding Dalam Menyelesaikan Soal Sistem Persamaan Linear Dua Variabel - Lusi Luthfia; Luvy Sylviana Zanthy (Journal on Education, 2019)
Errors made by students in solving SPLDV problems based on Kastolan stage, identify the factors - causes, and analyze the scaffolding that can be used to handle it. The method used is qualitative descriptive with the sample of this study taken using a purposive sampling technique from the population of all students of class VIII Mts in one of West Bandung Kab in the academic year 2018/2019. Data collection techniques using documentation, text, and interview techniques. Data analysis techniques are carried out through the process of data reduction, data presentation, and conclusion drawing. Based on the results of data analysis, it was concluded that there were 9.4% of students who made conceptual errors, 27.2% were procedural errors, and 22.8% had experienced technical errors. The internal factor that caused the error was because students were not careful, lacked training in the problem, lacked understanding of the prerequisite material, lacked understanding of the concept of solving two linear variables, and lacked understanding of the basic concepts of elimination and substitution methods. Scaffolding that can be given is explaining, reviewing, restructuring, and developing conceptual thinking